Corrigendum to 'Impact of the coronavirus disease 2019 (COVID-19) pandemic on the care of patients with acute and chronic aortic conditions': [Eur J Cardiothorac Surg 2020; doi.org/10.1093/ejcts/ezaa452] - Czerny, Martin; Gottardi, Roman; Puiu, Paul; Bernecker, Oliver Y; Citro, Rodolfo; Corte, Alessandro Della; di Marco, Luca; Fink, Martina; Gosslau, Yvonne; Haldenwang, Peter Lukas; Heijmen, Robin H; Hugas-Mallorqui, Maria; et al. (European journal of cardio-thoracic surgery, 2021)
In the original version of this article, the first name of author Vitaly Sorokin was misspelled. This has now been corrected above and in the full article.
Published: 11 August 2021
Gesehen am 20.08.2021